Mekanisme Penanganan Pembiayaan Bermasalah Pada Produk KPR Syariah Bank Sumut Syariah KCP Kota Baru Marelan - Khairina Tambunan; Muhammad Sandi (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The researcher is interested and aims to investigate and analyze the mechanism for handling problematic financing implemented by Bank Sumut Syariah, especially at KCP Kota Baru Marelan. This research adopts a type of field research with a focus on phenomena or symptoms that occur in the field related to problematic financing in Sharia Home Ownership Credit (KPR) products provided by PT. Bank Sumut Syariah, especially at the Sub-Branch Office (KCP) Kota Baru Marelan. The results of this research are based on observation and scientific logical analysis of data collected from the field. Based on in-depth discussions, Bank Sumut Syariah, especially at KCP Kota Baru Marelan, has implemented a mechanism for handling problematic financing by paying attention to sharia principles. This process involves proactive communication, involvement of sharia experts, and customer openness. Customers, as represented by Mrs. Nilam Kurnia, gave positive testimony regarding the bank's approach in handling problematic financing.